Who Disciplines Bank Managers? - Maechler, Andrea (IMF Working Papers; Working Paper, 2009)
We bring to bear a hand-collected dataset of executive turnovers in U.S. banks to test the efficacy of market discipline in a 'laboratory setting' by analyzing banks that are less likely to be subject to government support. Specifically, we focus on a new face of market discipline: stakeholders' ability to fire an executive. Using conditional logit regressions to examine the roles of debtholders, shareholders, and regulators in removing executives, we present novel evidence that executives are more likely to be dismissed if their bank is risky, incurs losses, cuts dividends, has a high charter value, and holds high levels of subordinated debt. We only find limited evidence that forced turnovers improve bank performance.